“De volta para o* Casa”: adolescentes com múltiplas passagens em medida socioeducativa de internação (ECA, Art. 122) - Santos, Cléber Fernando dos (2020)
This research aims to identify factors common to young people who, after fulfilling the socio-educational institutionalization measure, return to the Casa Foundation Service Centers to replicate the same previously imposed measure. Thus, generating the phenomenon called multiple passages, or even commonly referred to as recidivism. The study aims to identify in the context of the concreteness of the lives of these young people which conditions or situations contributed to the return by analyzing the information produced and contained in the records of the respective young people, when admitted to the Casa Foundation for the second or third time